2018
DOI: 10.18632/oncotarget.25696
|View full text |Cite
|
Sign up to set email alerts
|

MGMT inhibition in ER positive breast cancer leads to CDC2, TOP2A, AURKB, CDC20, KIF20A, Cyclin A2, Cyclin B2, Cyclin D1, ERα and Survivin inhibition and enhances response to temozolomide

Abstract: The DNA damage repair enzyme, O6-methylguanine DNA methyltransferase (MGMT) is overexpressed in breast cancer, correlating directly with estrogen receptor (ER) expression and function. In ER negative breast cancer the MGMT promoter is frequently methylated. In ER positive breast cancer MGMT is upregulated and modulates ER function. Here, we evaluate MGMT’s role in control of other clinically relevant targets involved in cell cycle regulation during breast cancer oncogenesis. We show that O6-benzylguanine (BG),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
1
13
2
Order By: Relevance
“…SKBR3 cell line used in our study is an ER-α − cell line in terms of characteristics. When compared to other studies [17] [19] in which the relation between ER-α and MGMT gene is revealed, the low expression of MGMT gene expression in SKBR3 cell line is seen to correlate with a low ER-α expression level. As a result of this characteristic of SKBR3 cell line, it is thought that the absence of ER-α expression leads to a low level of MGMT expression and therefore, a positive effect of TMZ treatment.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…SKBR3 cell line used in our study is an ER-α − cell line in terms of characteristics. When compared to other studies [17] [19] in which the relation between ER-α and MGMT gene is revealed, the low expression of MGMT gene expression in SKBR3 cell line is seen to correlate with a low ER-α expression level. As a result of this characteristic of SKBR3 cell line, it is thought that the absence of ER-α expression leads to a low level of MGMT expression and therefore, a positive effect of TMZ treatment.…”
Section: Discussioncontrasting
confidence: 58%
“…The two-year survival rate was observed to be 26.5% in treatment with radiotherapy and TMZ, and 10.4% in radiotherapy alone [14]. In another study with breast cancer demonstrates that survival rates of MCF-7 cells, which has ER + character, decreased to 52% exposed to 644 µM TMZ treatment for 4 days [17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another tumor-suppressor gene we studied was MGMT, which functions in DNA repair (49), and whose aberrant promoter hypermethylation has been shown in one-third of breast cancer cases (28). Contrary to the elevatin of methylation of RASSF1A, SFRP1 and DCC promoter in at least one HNO-adapted breast cancer cell line, we observed that methylation of MGMT promoter was significantly reduced in MCF-7-HNO cells compared to the parentaI cell line.…”
Section: Discussionmentioning
confidence: 65%
“…KIF20A is found overexpressed at both the mRNA and protein levels than the normal counterparts in breast cancer [65][66][67] and also in several other cancers including gastric cancer [68], bladder cancer [69,70], pancreatic cancer [71][72][73], hepatocellular cancer [74], lung cancer [75], glioma [76], and melanoma [77]. The overexpression of KIF20A gene is significantly associated with the poor survival of breast cancer patient [65,66] and drug resistance [66,78].…”
Section: Gene Type Gene Namementioning
confidence: 99%